The Effects of Transcranial Electrical Stimulation on Opiate-Induced Analgesia in Rats - Ayla A Kabalak; Oytun O Senel; Nermin Gogus (Pain Research and Management)
BACKGROUND AND OBJECTIVES: Recent experiments have shown that transcranial electrical stimulation significantly increases the potency and duration of the analgesic effects of opioids in humans and rats. In the present study, the influence of transcranial electrical stimulation (TCES) on the analgesic effect of remifentanil hydrochloride (HCl) in rats was determined.